Evaluation of Corrosion Performance for D-Gun Sprayed T91 Steel under Simulated and Actual Bio-Fuel Fired Boiler Environment - Kumar, Manoj (My University, 2017)
The Purpose of this work is to enhance the corrosion characteristics of coatings. 80Cr3C2–20NiCr and 88WC-12Co coatings were deposited on T91 boiler tube steel by the process of Detonation Gun. Oxidation and hot corrosion studies were conducted on bare and D-Gun coated T91steel specimens after applying molten salt (40Na2SO4, 40K2SO4, 10NaCl & 10 KCl) at 800°C under 50 cyclic conditions respectively. Each cycle consisted 1 hour of heating in the tubular furnace and 20 min of cooling of the sample at room temerature.After each cycle weight of each sample was measured by using digital weighing balance. Study under actual biofuel fired boiler enviroment. (SEM) scanning electron microscopy, (EDS) energy dispersive spectroscopy and X ray diffraction (XRD) techniques were used to analyze the corrosion product. The bare steel specimen experienced higher weight gain, which may be due to the occurrence of unprotective Fe2O3 dominated oxide scales. The WC-Co also does not performed well as it delaminates from the substrate when exposed to higher temperature after few cycles, The Cr3C2–NiCr coating was found to be more protective than WC-Co the coating. The phases disclosed in the oxide scale of the coated specimens were mainly oxides and spinels of nickel and chromium, which are reported to be protective against corrosion.
Keywords: Detonation gun, Corrosion, Boiler